PENGARUH ASIMETRI INFORMASI, LOCUS OF CONTROL, NILAI PERSONAL DAN SISTEM IMBALAN TERHADAP TERJADINYA BUDGETARY SLACK - Lunadewi, Ni Wayan Venti; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
The purpose of this study to determine the effect of information asymmetry, locus of control, personal value and reward systems against budgetary slack. In this study, the samples taken were 60 respondents from 14 Hotel Star 3, 4 and 5 in Denpasar which served as a manager, supervisor accounting department, supervisor of food and beverage department, supervisor engineering department, supervisor room department, supervisor kitchen department, and HRD department supervisor involved in the preparation of the budget on the Star 3, 4 and 5 in the city of Denpasar. Analysis techniques in the study of linear regression. The results showed that the variable asymmetry of information has a positive influence on budgetary slack, locus of control have a negative influence on budgetary slack, personal values have a positive influence on budgetary slack and the reward system positively affects budgetary slack.
Keywords: Information Asymmetry, Locus of Control, Personal Value, Reward Systems, Budgetary Slack